Gamma-glutamyl transpeptidase (γ-GTP) has an ambivalent association with hypertension and atherosclerosis among elderly Japanese men: a cross-sectional study - Yuji Shimizu; Shin-Ya Kawashiri; Kairi Kiyoura; Kenichi Nobusue; Hirotomo Yamanashi; Yasuhiro Nagata; Takahiro Maeda (Komiyama Printing Co. Ltd, 2019)
Abstract Background Even though there is bidirectional association between hypertension and atherosclerosis, atherosclerosis itself is involved in the process of endothelial repair. To clarify the association of endothelial repair with hypertension, a cross-sectional study was conducted. Methods We conducted a cross-sectional study of 562 elderly Japanese men aged 60-69. As gamma-glutamyl transpeptidase (γ-GTP) could act as a marker of oxidative stress that injures endothelial cell and higher levels of CD34-positive cell indicate a higher activity of endothelial repair, we therefore performed a CD34-positive level specific analysis of γ-GTP on atherosclerosis and hypertension. Results In the present study population, hypertension was independently and positively associated with atherosclerosis (multivariable odds ratio (OR) = 2.09 (1.30, 3.35)). Among participants with high CD34-positive cells, γ-GTP showed significant and positive association with atherosclerosis (OR of the log-transformed value of γ-GTP (OR) = 2.26 (1.32, 3.86)) but not with hypertension (OR = 0.77 (0.51, 1.17)). Among participants with low CD34-positive cells, even γ-GTP showed no significant association with atherosclerosis (OR = 0.92 (0.51, 1.68)), but was significantly and positively associated with hypertension (OR = 1.99 (1.27, 3.12)). Conclusions γ-GTP revealed to have ambivalent association with hypertension and atherosclerosis. Active endothelial repair that is associated with atherosclerosis might have beneficial association with hypertension.